Induction of Lymphocyte Transformation by Sequential Treatment with Neuraminidase and Galactose Oxidase - Novogrodsky, Abraham (1973)
Treatment of mouse-spleen cells with galactose oxidase (EC 1.1.3.9) after incubation with neuraminidase (EC 3.2.1.18) induced extensive blastogenesis. Treatment of the cells with galactose oxidase before incubation with neuraminidase had very little stimulatory effect. Either of these enzymes alone had practically no effect on the cells. The lymphocyte transformation induced by galactose oxidase in neuraminidase-treated cells was decreased upon reacting the cells with borohydride or hydroxylamine, whereas treatment with these compounds did not affect transformation of cells by concanavalin A. It is suggested that galactosyl residues exposed by the action of neuraminidase on the cell membrane are oxidized by galactose oxidase, and the aldehyde moiety thus formed is involved in the induction of blastogenesis.